Readiness of Kindergarten for Inclusive and Learning-Friendly Environment: Kesiapan Taman Kanak-Kanak untuk Lingkungan Inklusif dan Ramah Belajar - Amaliah, Gina; Mahabbati, Aini (Indonesian Journal of Innovation Studies, 2025)
General Background: Inclusive education is a global commitment to ensure equal learning opportunities for all children, including those with special needs. Specific Background: In Indonesia, inclusive early childhood education remains underdeveloped, especially in rural areas. Kindergarten Negeri 1 Sangkulirang provides a valuable case to explore readiness toward inclusivity. Knowledge gap: Previous studies on inclusive education largely focus on primary and secondary levels, with little attention to early childhood settings outside urban contexts. Aim: This study aims to examine the readiness of Kindergarten Negeri 1 Sangkulirang in creating an inclusive and learning-friendly environment for children with special needs. Results: The findings reveal that the school demonstrates strong commitment through open admission, flexible curriculum, and personalized learning plans. However, challenges persist in limited infrastructure, shortage of special assistant teachers, and insufficient collaboration with external experts. Cooperative communication between parents and teachers emerges as the main strategy for sustaining inclusivity. Novelty: This research provides insights into inclusive education practices at the kindergarten level in a remote area, highlighting both systemic and contextual factors. Implications: The study underscores the importance of teacher capacity building, systemic support, and integration of professional services to establish sustainable inclusive early childhood education. Highlight Commitment to inclusivity is shown through open admission and adaptive curriculum Challenges remain in infrastructure, staffing, and external professional collaboration Parent–teacher cooperation is central to sustaining inclusive learning Keywords Inclusive Education, Children With Special Needs, Kindergarten, Collaborative Strategies, Learning Environment